2010
DOI: 10.1002/lary.21098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking on taste: Assessment with contact endoscopy and taste strips

Abstract: Taste function presents significant resistance to smoking, although changes in morphology of fungiform and filiform papillae have been observed especially in heavy smokers. Laryngoscope, 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 20 publications
(30 reference statements)
3
19
1
2
Order By: Relevance
“…The extrinsic factors possibly affecting taste function comprise health and health‐behavior‐related factors, such as smoking, weight, diseases, and medication (Doets & Kremer, ; Doty, Shah, & Bromley, ; Fischer et al, ; Hardikar, Hoechenberger, Villringer, & Ohla, ; Pepino, Finkbeiner, Beauchamp, & Mennella, ). In contrast, there are also studies showing no associations between these factors and taste function (Fischer et al, ; Konstantinidis, Chatziavramidis, Printza, Metaxas, & Constantinidis, ; Methven et al, ; Mojet, Heidema, & Christ‐Hazelhof, ; Pepino et al, ). Thus, more studies that encompass all taste modalities are needed to better understand the factors affecting interindividual variations in taste perception.…”
Section: Introductionmentioning
confidence: 99%
“…The extrinsic factors possibly affecting taste function comprise health and health‐behavior‐related factors, such as smoking, weight, diseases, and medication (Doets & Kremer, ; Doty, Shah, & Bromley, ; Fischer et al, ; Hardikar, Hoechenberger, Villringer, & Ohla, ; Pepino, Finkbeiner, Beauchamp, & Mennella, ). In contrast, there are also studies showing no associations between these factors and taste function (Fischer et al, ; Konstantinidis, Chatziavramidis, Printza, Metaxas, & Constantinidis, ; Methven et al, ; Mojet, Heidema, & Christ‐Hazelhof, ; Pepino et al, ). Thus, more studies that encompass all taste modalities are needed to better understand the factors affecting interindividual variations in taste perception.…”
Section: Introductionmentioning
confidence: 99%
“…tarafın-dan yapılan bir çalışmada, ağır sigara içenlerde dildeki tat alma tomurcuklarının morfolojik yapısının değişmesine rağmen, tat alma fonksiyonlarında değişiklik olmadığı belirtilmiştir. 18 Araştırmamızda sigara içenlerin yemekleri hızlı tüketim oranı, sigara içmeyenlere göre daha yüksektir. Bu durum, sigara içenlerin, bir an önce sigara içebilmek için yemeklerini hızlı tüketmele-riyle açıklanabilir.…”
Section: Discussionunclassified
“…Just (2003) 13 found that the density of fungiform papillae varied among the investigated human subjects in different age groups. According to Chen (1998) 14 and Konstantinidis (2010), 15 the number of fungiform papillae showed no sex related differences. This aspect was not studied.…”
Section: Fungiform Papillaementioning
confidence: 94%